Highly Stable Complexes of Divalent Metal Ions (Mg2+, Ca2+, Cu2+, Zn2+, Cd2+, and Pb2+) with a Dota‐Like Ligand Containing a Picolinate Pendant. Issue 36 (13th November 2014) - Regueiro‐Figueroa, Martín; Ruscsák, Erika; Fra, Laura; Tircsó, Gyula; Tóth, Imre; de Blas, Andrés; Rodríguez‐Blas, Teresa; Platas‐Iglesias, Carlos; Esteban‐Gómez, David
Abstract: The stability constants of complexes of the macrocyclic ligand do3a‐pic 4– (H4 do3a‐pic = 2, 2′, 2″‐{10‐[(6‐carboxypyridin‐2‐yl)methyl]‐1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7‐triyl}triacetic acid) with several divalent metal ions (Pb 2+, Cd 2+, Zn 2+, Cu 2+, Ca 2+, and Mg 2+ ) have been determined by using pH‐potentiometric titrations ( I = 0.1M KCl, 25 °C). The stability of these complexes follows the trend Cu 2+  > Cd 2+  ≈ Pb 2+  ≈ Zn 2+  >> Ca 2+  >> Mg 2+ . A particularly high stability constant has been determined for the Cu 2+ complex [log  K CuL = 23.20(4)]. Analysis of the titration curves indicate the presence of protonated forms of the complexes in solution, with protonation constants of log  K M(HxL) = 6.9–2.0 ( x = 1, 2, or 3). The structure of the complexes in solution has been investigated by using 1 H and 13 C NMR spectroscopy and DFT calculations performed in aqueous solution at the TPSSh/6‐31G(d) level. In the case of the Pb 2+ and Cd 2+ complexes, relativistic effects were considered with the use of relativistic effective core potentials. Calculations show that the complexes with the largest metal ions (Pb 2+ and Ca 2+ ) are nine‐coordinate, with their coordination polyhedra being best described as capped twisted square antiprisms. The Cd 2+ and Mg 2+ complexes are seven‐coordinate, with the metal ions being bound to the four nitrogen atoms of the cyclen unit and the three acetate pendant arms. Finally, in the Cu 2+ and Zn 2+ complexes, the metal ions are six‐coordinated, with the metal ions being asymmetrically placed inside the macrocyclic cavity of the ligand, and the coordination polyhedra can be described as an octahedron and a trigonal prism, respectively. Abstract : A detailed study of the thermodynamic stability of complexes formed by divalent metal ions with a macrocyclic ligand containing a picolinate arm is reported. The complexes of Cu 2+, Zn 2+, Cd 2+, and Pb 2+ present high stability constants [log  K ML  > 20]. DFT calculations and NMR spectroscopy point to variable coordination numbers and geometries for this series of metal complexes.